Activation mechanisms and structural dynamics of STIM proteins - Sallinger, Matthias; Grabmayr, Herwig; Humer, Christina; Bonhenry, Daniel; Romanin, Christoph; Schindl, Rainer; Derler, Isabella (Journal of physiology (London. Print), 2024)
The family of stromal interaction molecules (STIM) includes two widely expressed single-pass endoplasmic reticulum (ER) transmembrane proteins and additional splice variants that act as precise ER-luminal Ca2+ sensors. STIM proteins mainly function as one of the two essential components of the so-called Ca2+ release-activated Ca2+ (CRAC) channel. The second CRAC channel component is constituted by pore-forming Orai proteins in the plasma membrane. STIM and Orai physically interact with each other to enable CRAC channel opening, which is a critical prerequisite for various downstream signalling pathways such as gene transcription or proliferation. Their activation commonly requires the emptying of the intracellular ER Ca2+ store. Using their Ca2+ sensing capabilities, STIM proteins confer this Ca2+ content-dependent signal to Orai, thereby linking Ca2+ store depletion to CRAC channel opening. Here we review the conformational dynamics occurring along the entire STIM protein upon store depletion, involving the transition from the quiescent, compactly folded structure into an active, extended state, modulation by a variety of accessory components in the cell as well as the impairment of individual steps of the STIM activation cascade associated with disease.
Keywords: protein STIM1; Calcium; vápník; Calcium Release Activated Calcium Channels; membránové proteiny; Calcium Signaling; ORAI1 Protein; vápníková signalizace; proteiny STIM; Membrane Proteins; Stromal Interaction Molecule 1; protein ORAI1; Stromal Interaction Molecules; kanály aktivované uvolněním vápníku